Assesment of the Mechanical Variability of Rock Slabs by Means of Non-Destructive Tests (2014)
In this article it is described a systematic test campaign —with the Schmidt- L-type rebound hammer— that was performed at a Sodalite slab of 0:05m thick in a square area of 2:0m of side. This research revealed that the studied ornamental rock has an inhe